SOME REGULARITIES IN HOMO GENUS EVOLUTION INFERRED FROM THE CRANIUM SPHERICITY DEGREE - Vangengeim E.A.; Pevzner M.A.; Pestryakov A.P. (My University, 1997)
The time dependence of the cranium sphericity degree of fossil humans from 48 sites in Europe, Asia, Africa, and Australia was studied. This parameter was established to follow the areacotangent law throughout the Pleistocene. Chronological intervals for all considered sites were determined by biometric dating. The intervals either completely or partially overlap with the published chronological data.
Keywords: Pleistocene; Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Плейстоцен